2017
DOI: 10.1096/fj.201601033r
|View full text |Cite|
|
Sign up to set email alerts
|

Glutamate oxaloacetate transaminase enables anaplerotic refilling of TCA cycle intermediates in stroke‐affected brain

Abstract: Ischemic stroke results in excessive release of glutamate, which contributes to neuronal cell death. Here, we test the hypothesis that otherwise neurotoxic glutamate can be productively metabolized by glutamate oxaloacetate transaminase (GOT) to maintain cellular energetics and protect the brain from ischemic stroke injury. The GOT-dependent metabolism of glutamate was studied in primary neural cells and in stroke-affected C57-BL6 mice using magnetic resonance spectroscopy and GC-MS. Extracellular Glu sustaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
55
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(55 citation statements)
references
References 35 publications
0
55
0
Order By: Relevance
“…Also Rink et al . () recently pointed out that, in ischemic conditions, glutamate‐oxaloacetate transaminase may be primarily involved in glutamate conversion into metabolic fuel, that is, α‐ketoglutarate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also Rink et al . () recently pointed out that, in ischemic conditions, glutamate‐oxaloacetate transaminase may be primarily involved in glutamate conversion into metabolic fuel, that is, α‐ketoglutarate.…”
Section: Discussionmentioning
confidence: 99%
“…; Rink et al . ). In this perspective, glutamate should be studied from a different point of view, because it is not only a neurotransmitter, but primarily a key metabolite for brain bioenergetics (Cooper ; Villa et al .…”
mentioning
confidence: 97%
“…Oxaloacetate was recently introduced as a neuroprotective drug [19-22] due to ability to decrease blood glutamate levels by the activation of the blood-resident enzyme glutamate-oxaloacetate transaminase (GOT). This enzyme catalyzes, by transfer of an amino group, the transformation of glutamate into α-ketoglutarate and of oxaloacetate into L-aspartate.…”
Section: Discussionmentioning
confidence: 99%
“…To that end, research efforts that have focused on the removal of pathologically elevated glutamate in the injured brain have been increasingly recognized for the therapeutic potential of glutamate removal to mitigate neurotoxicity (1)(2)(3)(4). Our laboratory has recently demonstrated the therapeutic potential of inducible glutamate oxaloacetate transaminase (GOT), a glutamate metabolizing enzyme that can repurpose otherwise neurotoxic glutamate in the stroke-affected brain as energy substrate for glucose-starved neurons (5)(6)(7). Specifically, GOT enables glutamate metabolism and the anaplerotic refilling of tricarboxylic acid (TCA; or the Krebs) cycle intermediates via at r u n c a t e dT C A cycle in the ischemic stroke-affected and, subsequently, hypoglycemic brain (6).…”
mentioning
confidence: 99%
“…Our laboratory has recently demonstrated the therapeutic potential of inducible glutamate oxaloacetate transaminase (GOT), a glutamate metabolizing enzyme that can repurpose otherwise neurotoxic glutamate in the stroke-affected brain as energy substrate for glucose-starved neurons (5)(6)(7). Specifically, GOT enables glutamate metabolism and the anaplerotic refilling of tricarboxylic acid (TCA; or the Krebs) cycle intermediates via at r u n c a t e dT C A cycle in the ischemic stroke-affected and, subsequently, hypoglycemic brain (6). Our observation identified that the correction of focal hypoxia during ischemic stroke induces GOT expression and rescues brain tissue from injury.…”
mentioning
confidence: 99%